Lichen genus Micarea Fr. in Asian Part of Russia. Sakha Republic (Yakutia) and Trans-Baikal Territory - L. A. Konoreva; S.V. Chesnokov; L.N. Poryadina (Altay State University, 2018)
Fourteen species of Micarea Fr. were found in the Sakha Republic (Yakutia) and nothern part of Trans-Baikal Territory. M. prasina and M. denigrata groups were identified by studiyng the lichen substances using standard technique of thin-layer chromatography (TLC) in solvent systems A and B. M. tomentosa Czarnota et Coppins is new to Eastern Siberia and M. incrassata Hedl. – to South Siberia. M. hedlundii Coppins, M. lignaria (Ach.) Hedl., M. tomentosa and M. incrassata are reported for the first time from Trans-Baikal Territory and M. elachista (Körb.) Coppins et R. Sant. – from Sakha Republic (Yakutia). M. cinerea (Schaer.) Hedl. and M. cf. pseudomarginata Coppins are given only according to literature data, because the original materials were unavailable to find or examined. Distribution in the territory of Sakha Republic (Yakutia) and Trans-Baikal Territory has been clarified for most of the listed species. Identification key, notes with diagnostic features and distribution data with maps for each species are provided. According to the results of our studies Asian part of Russia is much richer with lichens of the genus Micarea than it was previously known. Samples were deposited in the herbaria of Helsinki (H), the Komarov Botanical Institute (LE) and the Altai State University (ALTB).